2013
DOI: 10.1111/codi.12354
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment level of carcinoembryonic antigen on tumour downstaging and early occurring metastasis in locally advanced rectal cancer following neoadjuvant radiotherapy (30 Gy in 10 fractions)

Abstract: Pretreatment CEA level cannot only predict tumour downstaging and ypTNM stage for rectal cancer following 30 Gy/10 f nRT, but also promisingly suggests a high incidence of early occurring distant metastasis. These findings may be used to select patients with nRT resistance and occult metastasis and make alternative treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…A preoperative CEA level≥5 ng/mL was reported to be associated with the early distant metastasis [7,25]. In our study, sensitivity and PPV, NPV of CEA (82.14 %, 67.57 % and 83.3 %, respectively) was comparable with those of MRI-detected MVI (75.0 %, 89.47 % and 77.42 %) (P= 0.1379, 0.1467, and 0.5694).…”
Section: Discussionsupporting
confidence: 58%
“…A preoperative CEA level≥5 ng/mL was reported to be associated with the early distant metastasis [7,25]. In our study, sensitivity and PPV, NPV of CEA (82.14 %, 67.57 % and 83.3 %, respectively) was comparable with those of MRI-detected MVI (75.0 %, 89.47 % and 77.42 %) (P= 0.1379, 0.1467, and 0.5694).…”
Section: Discussionsupporting
confidence: 58%
“…The nRT regimen in the present study involved 30 Gy in 10 fractions, which is recommended by the Chinese Anti-Cancer Association and is designed to have a similar biological equivalent dose as a 5×5 Gy regimen and a prolonged interval of 2-4 weeks prior to surgery to increase the response rate and clinical efficiency. Our results reveal objective pathologic downstaging and response rates higher than those previously published for traditional short-course regimens [44][45][46]. The prognostic value of CD45RO + TILs following radiation is rarely reported in rectal cancer.…”
Section: Discussionsupporting
confidence: 39%
“…In this study, pre-CEA level was only significantly associated with distant metastasis and not local recurrence, which is verified by previous studies. 27 , 29 Park et al 27 showed that although perioperative CEA was a significant prognostic indicator for systemic recurrence, it was unable to predict locoregional recurrence in either stage II or III patients. Similarly, Wang et al 29 showed that the predictive value of pre-CEA on distant metastasis was more prominent in early systemic metastasis (within 6 months after surgery).…”
Section: Discussionmentioning
confidence: 99%